Patologická ložiska a zlomeniny proximálního femuru - Urban, M; Luňáček, Libor; Bartoška, Radek; Maléř, J; Skála-Rosenbaum, Jiří (Acta chirurgiae orthopaedicae et traumatologiae Čechoslovaca, 2023)
PURPOSE OF THE STUDY The aim of the study was to determine the incidence of primary malignancies metastasizing to the area of the proximal femur, to evaluate the localization of the lesions and fractures, to compare the results of the selected surgical therapy, survival time of the patients and postoperative complications. MATERIAL AND METHODS We retrospectively evaluated the group of patients operated on from 2012 to 2021. The study included 45 patients (24 women and 21 men) with a pathological lesion or a pathological fracture in the area of the proximal femur. The average age was 67 years (38-90). There were 30 (67%) cases of pathological fracture and 15 (33%) cases of pathological lesions in the cohort. In each patient, the perioperative biopsy or resected sample was sent for histological examination. The type of primary malignancy with the localization of lesions and fractures was assessed. Furthermore, we evaluated the outcomes of the surgical method chosen and its complications. We monitored the patients' functional score using the Karnofsky performance status and survival interval. RESULTS The most common primary malignancy was multiple myeloma in 10 cases (22%), followed by seven cases (16%) of breast and lung cancer and 6 cases (13%) of clear cell renal cell carcinoma. Internal fixation was used in 15 cases (33%). Tumor resection with hip joint replacement was performed in 29 patients (64%). One patient was treated with percutaneous femoroplasty. Out of a total of 45 patients, 10 patients (22%) survived for less than three months. The survival rate of more than one year was observed in 21 patients (47%). A total of seven complications occurred in six patients (15%). Fewer complications occurred in the group of patients with a pathological fracture compared to the group with an impending fracture. DISCUSSION Pathological lesions in the bone or an already existing pathological fracture are signs of advanced cancer. Better outcomes are reported in patients who underwent prophylactic surgery, which was, however, not confirmed by our study. The incidence of individual primary malignancies, the postoperative complications and the patient survival corresponded to the statistical data reported by the other authors. CONCLUSIONS In patients with a pathological lesion of the proximal femur, operative treatment will increase the quality of life, either when choosing osteosynthesis or joint replacement, while prophylactic treatment is usually associated with a better prognosis. As a less invasive procedure with lower blood loss, osteosynthesis is indicated for palliative therapy in patients with a limited expected survival time or in patients with a prognosis of healing of the lesion. Reconstruction of the joint with an arthroplasty is indicated in patients with a better prognosis or in cases excluding safe osteosynthesis. Our study confirmed good outcomes with the use of an uncemented revision femoral component. Key words: metastasis, osteolysis, pathological fracture, proximal femur.
Keywords: Female; femur; Quality of Life; kvalita života; mužské pohlaví; fraktury femuru; Retrospective Studies; fraktury spontánní; retrospektivní studie; Humans; Fractures, Spontaneous; nádory; Femoral Fractures; Postoperative Complications; lidé; senioři; vnitřní fixace fraktury; Femur; ženské pohlaví; Treatment Outcome; Aged; pooperační komplikace; Fracture Fixation, Internal; Male; výsledek terapie; Neoplasms